COGNITION, OPTIMISM, AND THE FORMATION OF AGE-DEPENDENT SURVIVAL BELIEFS - Nils Grevenbrock; Max Groneck; Alexander Ludwig; Alexander Zimper (International Economic Review, 2021)
This article investigates the roles of psychological biases for deviations between subjective survival beliefs (SSBs) and objective survival probabilities. We model these deviations through age-dependent inverse S-shaped probability weighting functions. Our estimates suggest that implied measures for cognitive weakness increase and relative optimism decrease with age. Direct measures of cognitive weakness and optimism share these trends. Our regression analyses confirm that these factors play strong quantitative roles in the formation of SSBs. Our main finding is that cognitive weakness instead of optimism becomes with age an increasingly important contributor to the well-documented overestimation of survival chances in old age.
Keywords: 330